Role of Social Media in Shaping the Political Perception of Youth in Tanggikiki Urban Village During the 2024 General Election - Moh. Yudha Mbuinga; Sastro M. Wantu; Udin Hamdin (Universitas Muhammadiyah Palu, 2025)
This study aims to understand the role of social media in shaping the political perception of youth in Tanggikiki Urban Village during the 2024 General Election. In the increasingly advanced digital era, platforms such as TikTok, Instagram, and Facebook serve not only as communication tools but also as instruments for political campaigns, spaces for political education, and platforms for expressing political views among young voters. This study uses a qualitative approach with a case study method. Data are collected through interviews, observations, and documentation from various informants, including young people, local officials, and members of the election supervisory committee. The findings reveal that social media plays an active role in shaping political opinions among the youth, encouraging participation in political discussions, and increasing awareness of electoral issues. However, negative impacts also arise, such as the spread of hoaxes, opinion polarization, and the creation of echo chambers that limit political perspectives. Therefore, digital literacy is essential for enabling youth to use social media critically and responsibly in support of a healthy democratic process.